The Influence of Overconfidence and Risk Perception on Investment Decisions: The Moderating Effect of Financial Literacy on Individual Millennial Generation Investors - Adlina Nadhila; Roy Sembel Roy Sembel; Melinda Malau (Green Publisher Indonesia, 2024)
Investment has evolved from a mere societal desire to a necessity, driven by the quest for higher returns in a shorter time frame. The millennial generation, being the largest population in its productive years, holds a significant role in investment activities. However, many millennials face challenges in achieving their expected investment results, possibly due to factors such as inadequate financial literacy, deficient risk management, and overconfidence in their investment decisions. This study aims to scrutinize the impact of financial literacy, risk perception, and overconfidence on investment decisions among millennials in Jakarta, offering insights to both investors and practitioners. By testing financial literacy as a moderator in the relationship between risk perception, overconfidence, and investment decisions, the research fills a literature gap. Through a quantitative survey of 200 millennial investors in Jakarta and PLS-SEM analysis, the study reveals that overconfidence and risk perception positively influence investment decisions. Additionally, financial literacy moderates the effect of overconfidence but not risk perception on investment decisions. The findings provide valuable guidance for investors, emphasizing the crucial role of financial literacy in mitigating irrational behavior during decision-making, thereby influencing investment choices.